Virtual Digital Libraries for Professional Education - Rakhmatullaev, Marat (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article is devoted actual problems of support of the system of professional education on the basis of development corporate network and virtual libraries of colleges. Some important results of applied researches on creation of the corporate network of Uzbekistan libraries are given. The information about the basic information sources (databases, multimedia encyclopedias and characteristics of other resources) actively used in educational process and virtual libraries are included too.